2006
DOI: 10.1200/jco.2006.07.9129
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of a Toll-Like Receptor 9–Activating Oligonucleotide in Patients With Metastatic Melanoma

Abstract: These results indicate that TLR9-targeted therapy can stimulate innate immune responses in cancer patients, identify biomarkers that may be associated with TLR9-induced tumor regression, and encourage the design of follow-up studies to evaluate the ability of this therapeutic approach to target human cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(111 citation statements)
references
References 28 publications
1
107
0
3
Order By: Relevance
“…Most likely, pDCs are not properly activated on uptake of tumor-derived substances because of the lack of danger signals (12). Recent studies have shown that in vivo TLR triggering with TLR-Ls, such as CpG, induced pDC activation, resulting in antitumor immunity and partial tumor regression (42)(43)(44). Furthermore, activated human pDCs pulsed with a tumor Ag primed IFN-g secreting Ag-specific CTLs (45).…”
Section: Discussionmentioning
confidence: 99%
“…Most likely, pDCs are not properly activated on uptake of tumor-derived substances because of the lack of danger signals (12). Recent studies have shown that in vivo TLR triggering with TLR-Ls, such as CpG, induced pDC activation, resulting in antitumor immunity and partial tumor regression (42)(43)(44). Furthermore, activated human pDCs pulsed with a tumor Ag primed IFN-g secreting Ag-specific CTLs (45).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both myeloid and pDCs were activated (Molenkamp et al, 2007), indicating that PF-3512676 clearly has immunomodulatory activity. In a different phase II study in patients (N ¼ 20) with metastatic melanoma treated with s.c. PF-3512676, two (10%) patients had a PR and three (15%) patients had stable disease (SD) (Pashenkov et al, 2006). These patients with possible clinical benefit from PF-3512676 therapy tended to have increased levels of NK cell activity compared to the patients with progressive disease.…”
Section: Skin Cancersmentioning
confidence: 99%
“…Three patients experienced stabilization of the disease, although all presented with progression at week 24. The markers of immunological activation showed increased DC activation with elevated levels of type I IFN, and induction of NK cell cytotoxicity [126]. A phase I/II trial was designed to assess the safety and efficacy of the Toll-like receptor 2/6 agonist MALP-2 in combination with gemcitabine in patients with incompletely resectable pancreatic carcinoma.…”
Section: Tlrs In Clinical Trials Against Human Malignanciesmentioning
confidence: 99%